Analisis Kedudukan Istri sebagai Pencari Nafkah Utama: Telaah dalam Perspektif Kompilasi Hukum Islam dan Maslahah mursalah - Yasid Amanulah; Hari Widiyanto; Muhammad Mustahal (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Social and economic changes in the modern era have led to shifts in household roles, including the phenomenon of wives becoming the primary breadwinners. This issue raises legal and social questions from an Islamic perspective, particularly under the Compilation of Islamic Law (KHI) and the concept of maslahah mursalah. This study aims to analyze the legal status of wives as primary breadwinners based on KHI provisions and the maslahah mursalah principle. The research employs a qualitative approach with normative analysis of Islamic legal regulations and concepts. The findings indicate that, under KHI, the husband is primarily responsible for providing for the family. However, under certain circumstances, the wife may assume this role while maintaining balance in the household. From the perspective of maslahah mursalah, this phenomenon is permissible as long as it brings benefits to the family and does not cause harm. Therefore, Islam provides flexibility in the division of financial responsibilities, ensuring justice and family welfare remain upheld.